SINTAGMATIK-PARADIGMATIK SYAHRUR DALAM TEKS AL-QURâ€™AN - Elkarimah, Mia Fitriah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
Contemporary muslim thinker mostly from Islamic dicipline, but not for Muhammad Syahrur (here in after referred as: Syahrur) who interested in islamic issue without Islamic background, can offers many ideas in his book, al-Kitab wa al-Qurâ€™an, this book is the first book published, â€œthis book is contemporer reading of interpreting the holy book of the Qurâ€™anâ€ by analysis of the 20th century; which means that his opinion of the Qurâ€™an must be interpreted according to the present methodology, Al -Qur'an is a revelation and guidance for mankind, so that the Qur'an can be understood as a whole for humans throughout the period naturally. From that then, the linguistic approach was used by Shahrur in digging up the secrets of His message. This research wants to explain format of Syahrurâ€™s linguistic approach which related laws of verses of the Qurâ€™an. Actually, discuss all his linguisticc approach are very interesting, but the writer just take the syntagmatic - paradigmatic analysis of the term al - istiqamah and al - Hanif. From this reasearch, there are two basic formulations problems, firstly how Shahrur analyze these two words by using syntagmatic - paradigmatic analysis and what advantages and disadvantages which offered Shahrur in this analysis. This reseach used library research models, and focus on analytical descriptions from his book by qualitative model.